The performance potential of wind energy in Ukraine and prospects for its recovery after the war - Балджи, М. Д.; Балджи, Марина Дмитрівна; Baldzhy, Maryna D.; Antoniuk, Nataliia; Perkhach, Оksana (My University, 2022)
he potential of wind energy in Ukraine is examined in this article. Possibilities of its use are analyzed, an analytical assessment of the potential for its use is performed, and prospects for the use of energy resources for the development of the wind energy market is substantiated. Reasons are provided for the advantages and disadvantages of wind energy, which should be combined into the following components. The natural resource potential of Ukraine for the development of wind energy is analyzed. It has been confirmed that the wind energy potential of different territories of Ukraine is characterized by average annual wind speeds at the level of 7.0–8.5 m/s (on the continent – at heights of about 100 m, in water areas – about 50 m), which allows using megawatt-class wind turbines with annual coefficients of capacity utilization at the level of 0.3–0.4, which is quite efficient. The specific energy potential of wind energy in Ukraine is established, according to which, the territories of the country were grouped. It has been specified that the best places for locating wind power plants are areas with strong and constant winds, which can be found on the coast of the seas and in mountainous areas. The situation with the production of energy resources in Ukraine is analyzed based on wind sources and means before the war. The advantages of wind energy development based on the improvement of legislative framework and promoting production of equipment for the operation of wind power plants in Ukraine are proven. The reasons for the potential of the wind energy market are stated and the main consumers of wind energy in Ukraine are outlined. The development of wind energy is considered as a method for energy independence of the national economy of Ukraine.
Antoniuk N. The performance potential of wind energy in Ukraine and prospects for its recovery after the war / N. Antoniuk, M. Baldzhy, О. Perkhach // Polityka energetyczna – Energy policy journal. – 2022. – Vol. 25, Issue 3. – Р. 91-104. DOI: 10.33223/epj/153978
Keywords: wind energy; potential; energy resources; market; national economy; Research Subject Categories::SOCIAL SCIENCES::Business and economics; Research Subject Categories::TECHNOLOGY